Value of a structured information literacy course: a case analysis - Sajjad ur, Rehman; AlAwadhi, Suha; Rehman, Sajjad ur; AlAwadhi, Suha (Malaysian Journal of Library and Information Science, 2017)
ur Rehman, S., & AlAwadhi, S. (2013). Value of a structured information literacy course: a case analysis. Malaysian Journal of Library & Information Science, Vol.18, no. 1: 27-37. The College of Social Sciences at Kuwait University introduced a 3-credit hour formal course of information and computing literacy as a required course for the undergraduate students. Four years back, the course structure and content were revised and the component of inquiry was added to the same course. This course has been in place for more than a decade. This study was designed to assess the relevance and usefulness of this course for developing the needed computing, information and inquiry capabilities among students. The study was thus designed to investigate; firstly, whether the course had made any significant difference in the computing, information and research capabilities of students. Secondly, it assessed whether certain personal and social variables of students were associated with significance differences in student capabilities. A research instrument was designed around the constructs that had been defined in the course description and syllabi of 1380-131. This instrument was administered in the first week of the Semester 1 classes of the year 2009-10 in five sections of the same class. The same instrument, with changed facts and multiple-choice statements, was administered in the last week of the same semester in the same five sections. Students also provided information about personal and social variables. It was found that the students performed significantly better for the overall information literacy and for the three segments of information, computing and research. Academic majors of students, types of schools they had attended and mother’s academic qualifications were found to be associated with significant differences in students’ performance on information literacy measures.